Τὴν ἐκβολὴν τοῦ λόγου ἐποιησάμην: Thucydides’ Chronicle in the Pentekontaetia (1.97–117) is not a Digression - Rusten, Jeffrey S. (Histos, 2020)
Τὴν ἐκβολὴν τοῦ λόγου ἐποιησάμην (1.97.2) means not ‘I made a digression in my narrative’ but is rather a periphrasis for τὸν λόγον ἐξέβαλον, ‘I have discarded my logos’ (here ‘plan’). It sets aside the Corcyra starting-point announced at 1.23.5–6, interrupted by listing the empire’s much earlier military actions following the league’s foundation. Two old objections are reconsidered. (1) ‘1.88 begins the flashback, so 1.97.2 is not a break’. 1.88–96 is, however, an orderly digression linked to Sparta’s war-vote, extending Herodotus 9.102–12 to the Delian League. 1.97.2 refuses to return to the main narrative. (2) ‘1.97.2 is a jumble of unrelated statements.’ Yet every sentence references τοσάδε/αὐτά, the upcoming content. This first-person preface reflects both its purpose in itself (filling a large gap, replacing Hellanicus) and within Book 1 (changing plan, documenting empire). After the chronicle Thucydides retraces his steps: 1.118 concatenates segments totaling fifty years, repeats 1.97.2, then 1.88, finally resuming 1.87.6 where his initial narrative broke off. 1.97.1 and 1.118 resemble 5.26, where the narrative-period is again extended, another gap filled, and multiple narratives again concatenated. 1.97.2 need not prove a later stage of composition: ‘Spartan fear’ of Athens is prominent (but not to be narrated) in 1.23.6 and later (unless we implausibly remove these as later insertions also).